An asymmetrical dual band bandpass filter. Issue 1 (January 2017) - Malherbe, J.A.G.
ABSTRACT: A dual band bandpass filter consisting of a cascade of unit elements and shunt connected stepped open and stepped short circuited stubs, is described. The dual passbands can have unequal, asymmetrical width; the stop‐bandwidth between the desired bands and the harmonic upper bands is substantially increased. A prototype filter that finds application in communication systems is developed. © 2016 Wiley Periodicals, Inc. Microwave Opt Technol Lett 59:163–168, 2017